Ethnobotic Study Of Medicinal Plants In Suranadi Village, West Lombok Regency - Gitta Safitri Idmulya Ade Kayanti; Niechi Valentino; Rahmat Mulyadin (Ecobios Journal Of Environmental Science, 2024)
Ethnobotany is an interaction between society and its environment, specifically referring to plants and the study of their utilization. The purpose of this study was to determine the types of medicinal plants utilized by the community in Suranadi Village. Data collection through in-depth interviews to obtain information about the types of medicinal plants used and direct observation in the field. Based on the results of the study, 47 plant species from 33 families were obtained that were utilized as traditional medicine. The most numerous family is Zingiberaceae with a percentage of 9%. The most widely utilized part of the plant is the leaves as much as 53%. Plant habitus is dominated by herbs as much as 32%, and the status of plants used as medicine is mostly cultivated as much as 68% with the most common processing method, namely by boiling and then drinking.